Les conseillers et l'évaluation de leurs services: préliminaires sur leur attitude - Paré, Maryse; Lecomte, Conrad (Canadian Journal of Counselling and Psychotherapy, 2012)
The importance of evaluating psychological services is emphasized, both by society and by the profession itself. In practice, not much evaluation is actually done for a variety of reasons, among which are the attitudes of counsellors themselves towards evaluation of their services. The theoretical orientation is an important descriptive variable of counsellors and therefore its influence on such attitudes was studied. A Questionnaire on the Evaluation of Services (Q.K.S.) was answered by 854 experienced counsellors, members of the Professionnal Corporation of Psychologists of Québec (C.P.P.Q.). Data analysis indicates that their attitudes mainly comprise "the openness to evaluation" and "skills and resources available". It was found that theoretical orientation has a minor influence on these attitudes. Considerations on the application of evaluation procedures are discussed.